Recent Study on Treatment of Glucocorticoid Steroid Resistant Chronic Inflammatory Disease with Moxa Tar - Qian Zeng (Challenges in Disease and Health Research Vol. 7, 2021)
Currently glucocorticoid steroid is the mainstay of treatment of chronic inflammatory diseases like asthma, COPD, rheumatoid arthritis. But many chronic inflammatory diseases are resistant to glucocorticoid steroid like pulmonary fibrosis, atherosclerosis related diseases, chronic laryngitis and chronic muscle injury. Glucocorticoid steroid has been thoroughly studied and its therapeutic potential has been exhausted, and therefore there is a need to develop new anti-inflammatory drugs or anti-inflammatory therapies. Moxa (Artemisia Argyi) is a plant, its burning smoke or tar has strong anti-inflammatory property. In this article the author wants to introduce a new way (moxa tar) of treating glucocorticoid steroid resistant chronic inflammatory diseases based on some clinical experiments and hypothesis of the author’s personal observation. The purpose of this article is to open up a new field and raise researchers’ attention to this new field for developing new anti-inflammatory drugs or anti-inflammatory therapies. The methods used in this study are Crossover design, i.e. patients serve as their own control, comparing the clinical symptoms and signs before and after moxa tar treatment.